2020
DOI: 10.3389/fmicb.2020.562814
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Cell Type-Dependence on the Arenavirus Z-Mediated Virus-Like Particle Production

Abstract: Several arenaviruses are highly pathogenic to humans, causing hemorrhagic fever. Discovery of anti-arenavirus drug candidates is urgently needed, although the molecular basis of the host-and organ-specific pathogenicity remains to be fully elucidated. The arenavirus Z protein facilitates production of virus-like particles (VLPs), providing an established method to assess virus budding. In this study, we examined the efficiency of VLP production by solely expressing Z protein of several different arenaviruses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…It has been indicated that the activation of P (T/S)AP motifs in the HRS subunit of ESCRT-0 can recruit ESCRT-1 TSG101 via binding of the P(T/S) AP motif with the UEV domain of TSG101 [ 152 ]. The similar structure of the P (T/S) AP motif has been indicated within viral Gag protein from Retroviridiae (such as HIV and murine leukemia virus), Z proteins of Arenaviridae (Lassa virus and lymphocytic choriomeningitis virus), VP40 proteins of Filoviridae (Ebola virus and Marburg virus), and M (Matrix) proteins of Rhabdoviridae (vesicular stomatitis virus and rabies virus) [ 153 157 ]. These factors can activate TGG101, leading to the participation of the ESCRT complex at the site of virus entry [ 149 ].…”
Section: Entry Pathway Of Virusesmentioning
confidence: 75%
See 1 more Smart Citation
“…It has been indicated that the activation of P (T/S)AP motifs in the HRS subunit of ESCRT-0 can recruit ESCRT-1 TSG101 via binding of the P(T/S) AP motif with the UEV domain of TSG101 [ 152 ]. The similar structure of the P (T/S) AP motif has been indicated within viral Gag protein from Retroviridiae (such as HIV and murine leukemia virus), Z proteins of Arenaviridae (Lassa virus and lymphocytic choriomeningitis virus), VP40 proteins of Filoviridae (Ebola virus and Marburg virus), and M (Matrix) proteins of Rhabdoviridae (vesicular stomatitis virus and rabies virus) [ 153 157 ]. These factors can activate TGG101, leading to the participation of the ESCRT complex at the site of virus entry [ 149 ].…”
Section: Entry Pathway Of Virusesmentioning
confidence: 75%
“…The interaction promotes the ubiquitylation using NEDD4, as an ESCRT auxiliary protein, leading to the sorting of proteins into the MVBs [ 162 ]. Of note, a PPXY-like motif exists in several viruses from different families such as Retroviridiae, Rhabdoviridae [ 157 ], Arenaviridae [ 153 ], Filoviridae [ 156 ], Reoviridae [ 149 ], Hepadnavirideae [ 149 ], and Paramyxoviridae [ 159 ]. Similarly, the interaction of PPXY-NEDD4 increases the budding of the virus into the MVBs.…”
Section: Entry Pathway Of Virusesmentioning
confidence: 99%
“…Another important fact with arenaviruses is that most of these have been found a late domain, in the original arenaviruses, as mentioned, the Lassa virus contains two late domains PTAP and PPXY, while the Lujo virus only shows PSAP. Modern viruses such as Junin, Machupo, Guanarito, Sabia, and Chapare contain the PT/SAP domain and in this same context of viruses, it was found that the White Water Arroyo virus (WWAV) and Pichinde virus contain overlapping domains of PT/SAP and motifs similar to PPPY, with PT/SAPPY similar to those seen with Ebola [ 84 , 85 ]. The Hepatitis A virus was recently found to contain in its VP2 protein the YPX n L domain, and replacing Leu with Ala in the late domain eliminates virus release but does not alter viral assembly.…”
Section: Late Domainsmentioning
confidence: 99%
“…In addition to this, the fact that the sole expression of Z protein induces the release of VLPs in the absence of other viral components [95,96,185], allowed the discrete study of viral morphogenesis and/or egress, independently of viral entry and replication [93,97,110,181]. Of note, it has been recently tested that JUNV Z efficiently produces VLPs in a variety of cell lines, unlike TCRV, which showed limited cell-type restrictions for the budding process [245]. In sum, all these cell-based systems described above have strongly helped to dissect different aspects of the viral life cycle of JUNV and related arenaviruses and have provided insights of JUNV interaction with cell host factors.…”
Section: Alternative Systems To Evaluate Junv Replication Assembly An...mentioning
confidence: 99%